Analisis Persepsi Mahasiswa Terhadap Kompetensi Dosen Universitas Panca Bhakti Pontianak - Adi Mursalin; Delvi Defitri (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2021)
This thesis entitled "Analysis of Students' Perceptions of the Lecturers' Competencies of Panca Bhakti University Pontianak" with the aim of knowing and analyzing students' perceptions of the competence of Lecturers at Panca Bhakti University Pontianak. In this study the authors used the right method so that this research was headed towards the right target. The method used in this research is a survey method that goes directly to the field by distributing questionnaires to 97 respondents. To facilitate the measurement of quantitative data, the class interval scale is used. In this study, the variables that became the benchmarks for the authors to analyze the problems in this study were 4 variables, namely: Pendagogic Competence, Personality Competence, Social Competence, and Professional Competence. When viewed from the results of the study, the Analysis of Student Perceptions of the Competence of Lecturers at Panca Bhakti University Pontianak based on respondents' responses falls into the Good category value.